The Logic of Δ. (3rd January 2014) - Christensen, Ryan
<x xml:space="preserve">Abstract</x> I argue that the 'aoristic' operators, which are intended to describe the logic of vagueness, do not form a standard modal logic. I redefine the operators so that they do form a standard modal logic, provide a semantics of that logic, and argue that the logic is not as strong as standardly claimed.